2018
DOI: 10.1002/mop.31234
|View full text |Cite
|
Sign up to set email alerts
|

Design of wide‐beam triple‐fed helical antennas employing simple and efficient feed networks for bandwidth improvement

Abstract: In this article, a simple method for designing feed networks for wide-beam multi-fed helical antennas, suitable for satellite communications, is studied. Power division with similar phase differences for these antennas is obtained using serial feed network. The number of antenna arms is arbitrary, since the serial feed can be designed for any feasible number of outputs. Triple-fed helical antenna is studied in this article, as an example. The proposed S band triple-fed antenna benefits from 3 dB AR bandwidth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In recent years, a number of methods to broaden antenna bandwidths have been studied and reported. In Reference , helix antennas with heart‐shaped patterns have been studied widely for use in the satellite navigation field. A triple‐fed helical antenna for application to S‐band communication was researched with the aim of enhancing its axial‐ratio (AR) bandwidth; the four arms of the helix with coupled lines were analyzed in efforts to broaden the beamwidth, and a quarter‐wavelength printed structure was used to reduce the antenna profile.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a number of methods to broaden antenna bandwidths have been studied and reported. In Reference , helix antennas with heart‐shaped patterns have been studied widely for use in the satellite navigation field. A triple‐fed helical antenna for application to S‐band communication was researched with the aim of enhancing its axial‐ratio (AR) bandwidth; the four arms of the helix with coupled lines were analyzed in efforts to broaden the beamwidth, and a quarter‐wavelength printed structure was used to reduce the antenna profile.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference , helix antennas with heart‐shaped patterns have been studied widely for use in the satellite navigation field. A triple‐fed helical antenna for application to S‐band communication was researched with the aim of enhancing its axial‐ratio (AR) bandwidth; the four arms of the helix with coupled lines were analyzed in efforts to broaden the beamwidth, and a quarter‐wavelength printed structure was used to reduce the antenna profile. While the half‐power beamwidth (HPBW) of the antenna in Reference can reach 176°, its impedance bandwidth (IBW) is narrow and the antenna's profile is too large to be integrated within the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconfigurability can be applied on the operating frequency, beam direction, polarisation and so on [1][2][3][4]. Also, a simple and efficient feeding method for obtaining a wideband circularly polarised antennas has been developed recently for circular patch antennas, helical antennas and inverted-F antennas [5][6][7]. The idea is indeed based on the sequentially rotated serial feed for a single antenna [8,9].…”
mentioning
confidence: 99%
“…In this Letter, the possibility of using the sequentially rotated serial feed for constructing circular polarisation (CP) reconfigurable antennas is studied. This kind of feeding network is capable of producing CP in a wide frequency band by producing the same angular and phase differences for the outputs [5,6]. It is indicated that the CP reconfigurable antennas can be constructed by employing the serial feed with three probes, explicitly.…”
mentioning
confidence: 99%